An exploration of the efficiency of the Shenzhen Stock Exchange - Lu, Hongjie (2007)
This study has explored weak and semi-strong form efficiency for only A shares traded on the Shenzhen Stock Exchange using daily data for top 100 individual firms for the period 2004 to 2007. The first part, for the test of market efficiency in the weak form, two traditional tests will be applied, it should be mentioned that these two tests are strong in the sense of random walk (both tests are random walk tests), the results indicated that the Shenzhen A shares are slightly deviations from the random walk, when the serial correlation coefficient test is applied. But from the runs test, the result showed completely random walk pattern. The second part, for the test of semi-strong form efficiency, the cross-sectional regression is applied; the results indicate the betas lack explanatory power even when its effect is examined alone in the regression. Moreover, the finding also revealed a significant cross sectional relationship between the fundamental factors (book-to-market ratio and P/E ratio) and the expected stock returns. The P/E ratio has the most significant effect in the expected stock returns over the period 01,07,2004 to 30, 09, 2006. The book-to-market ratio also has fairly significant effect in the expected stock returns. Finally, the results suggested the firms with lower BM and P/E ratio attempt to earn higher average returns.